MicroRNA-3613-5p Promotes Lung Adenocarcinoma Cell Proliferation through a RELA and AKT/MAPK Positive Feedback Loop - Tao He; Hongyou Shen; Shuangmiao Wang; Yanfang Wang; Zhiwei He; Litong Zhu; Xinyue Du; Dan Wang; Jiao Li; Shizhen Zhong; Wenhua Huang; Huiling Yang (Elsevier, 2020)
Aberrant activation of nuclear factor κB (NF-κB)/RELA is often found in lung adenocarcinoma (LUAD). In this study, we determined that microRNA-3613-5p (miR-3613-5p) plays a crucial role in RELA-mediated post-transcriptional regulation of LUAD cell proliferation. Expression of miR-3613-5p in clinical LUAD specimens is associated with poor prognosis in LUAD. Upregulation of miR-3613-5p promotes LUAD cell proliferation in vitro and in vivo. Our results suggested a mechanism whereby miR-3613-5p expression is induced by RELA through its direct interaction with JUN, thereby stimulating the AKT/mitogen-activated protein kinase (MAPK) pathway by directly targeting NR5A2. In addition, we also found that phosphorylation of AKT1 and MAPK3/1 co-transactivates RELA, thus constituting a RELA/JUN/miR-3613-5p/NR5A2/AKT1/MAPK3/1 positive feedback loop, leading to persistent NF-κB activation. Our findings also revealed that miR-3613-5p plays an oncogenic role in LUAD by promoting cell proliferation and acting as a key regulator of the positive feedback loop underlying the link between the NF-κB/RELA and AKT/MAPK pathways.